E-Learning in Childhood Education: A Roadmap for Effective Management of Schools - Goodhope Chinenye Igwe (Researchparks Publishing, 2022)
The dynamic changes and technological advancements in the world today coupled with their attendant challenges create a drive for innovation in childhood education to achieve better and lasting results. This material examines e-learning as a strategy for achieving cognitive development and effective management of schools. It identifies the techniques used in e-learning which include the use of internet, CD-ROM (audio lessons/ audio books, video books, interactive videos) and the virtual classroom. It also identifies the differences between e-learning and traditional classroom learning. The impact of E-learning on the cognitive development of children is considered as well as the benefits and disadvantages of e-learning, which if properly managed would provide outstanding results in childhood education, effective management of the educational enterprise and sustainable development.